2023
DOI: 10.3390/molecules28031476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoquercitrin on Free Fatty Acid-Induced Lipid Accumulation in HepG2 Cells

Abstract: Liver metabolic disorders and oxidative stress are crucial factors in the development of nonalcoholic fatty liver disease (NAFLD); however, treatment strategies to combat NAFLD remain poorly established, presenting an important challenge that needs to be addressed. Herein, we aimed to examine the effect of isoquercitrin on lipid accumulation induced by exogenous free fatty acids (FFA) using HepG2 cells and elucidate the underlying molecular mechanism. The cells were exposed to 0.5 mM FFA to induce intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…This hypothesis relies on several facts: (1) the miRNA mechanism of action after mRNA interaction is mainly inhibitory [18], and (2) QKI and MAPKAPK2 inhibitions have been positively correlated with the prevention and/or counteraction of metabolic homeostasis disturbances including lipid alterations [34,37]. To validate this hypothesis, we used human hepatocytes (HepG2 cells) loaded with a mixture of FFAs (oleic and palmitic acids) as a model to mimic hepatic steatosis in vitro; this model was previously used in the study of plant bioactive compounds regulating lipid metabolism [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis relies on several facts: (1) the miRNA mechanism of action after mRNA interaction is mainly inhibitory [18], and (2) QKI and MAPKAPK2 inhibitions have been positively correlated with the prevention and/or counteraction of metabolic homeostasis disturbances including lipid alterations [34,37]. To validate this hypothesis, we used human hepatocytes (HepG2 cells) loaded with a mixture of FFAs (oleic and palmitic acids) as a model to mimic hepatic steatosis in vitro; this model was previously used in the study of plant bioactive compounds regulating lipid metabolism [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…To measure cellular lipid deposition, Oil Red O staining (Sigma-Aldrich) was performed as previously described ( Kim et al ., 2023 ). To quantify Oil Red O content, dimethyl sulfoxide (DMSO) was added to each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicate that USM from SKK and SMC reduces lipid accumulation by inhibiting the expression of the lipogenic proteins, including FAS and SREBP- To examine the effects of USM on lipid accumulation, HepG2 cells were treated with FFA and various concentrations of USM for 24 h. However, treatments with USM from SKK or SMC significantly inhibited FFA-induced fat accumulation (Figure 2A,B). In recent studies, the exposure of HepG2 cells to FFA increased lipid accumulation [38][39][40]. A previous study showed that wheat germ extract suppresses lipid accumulation in palmitic-acid-treated HepG2 cells [41].…”
Section: Effects Of Usm On Lipid Accumulation and Lipogenesismentioning
confidence: 98%